The Fractionation Properties of Human Factor VIII (Antihaemophilic Factor) - Gobbi, Franco (Thrombosis and Haemostasis, 1960)
The fractionation properties of human Factor VIII (antihaemophilic factor, AHF, antihaemophilic globulin) have been studied using a plasma of congenital afibrinogenaemia as a starting material.From a fibrinogen-free plasma, Factor VIII does not precipitate with ethanol at a final concentration of 8%; on the contrary the maximum yield is reached at an ethanol concentration of 25%.With a precipitation method carried out by a one to ten dilution of plasma with distilled water and acidification by N/10 hydrochloric acid to a pFI 5.2, Factor VIII does not precipitate with the euglobulin fraction; when normal plasma is used, such a precipitation is almost complete.With the salting-out fractionation method by ammonium sulphate, Factor VIII precipitates at a concentration between 25 and 33% of saturation either from fibrinogen-free and from normal human plasma.A non-specific thromboplastic activity appears in the fractions prepared by every method. This activity, which is probably due to the activation of seric accelerators, is easily removed by Al(OH)s adsorption. Thus, in order to insure the specificity of Factor VIII assays, the preliminary adsorption of the fractions is indispensable before testing their antihaemophilic activity.Fibrinogen and Factor VIII have different and definite precipitation patterns. When these two factors are associated the fractionation properties of AHF appear quite modified, showing a close similarity to those of fibrinogen. This fact can explain the technical difficulties encountered in the attempt to purify the antihaemophilic factor, and the lack of reproducible procedures for removing fibrinogen without affecting Factor VII.